Comparative Cytomorphometric Study of Exfoliated Oral Epithelial Cells from a Population of Smokers, Tobacco Users and Gutkha Chewers - Nishant; Sharma, Bhagwat Swaroop (Journal of College of Medical Sciences-Nepal, 2022)
Introduction: Tobacco remains one of the most important preventable cause of addiction, sickness and mortality in the world as it affects the oral epithelium. Normal epithelium undergoes continuous exfoliation or shedding of its superficial cells, and it is replenished by new crop of cells from the basal layer. The rationale of exfoliative cytology lies in the epithelial physiology. The purpose of this study is to conduct quantitative cytomorphometric studies on squames obtained from a population of Tobacco and Gutkha users, to assess the cytomorphometric changes in Nuclear Area (NA) and Cytoplasmic Area (CA) of squames from tobacco smokers, tobacco chewers, gutkha chewers, to compare the results with control group normal healthy individuals and among themselves. Methods: Oral smears were taken from buccal mucosa of total 200 individuals. The smears were histochemically stained and cytomorphological assessment was done. Groups were compared by one way analysis of variance (ANOVA) and the significance of mean difference between the groups was done by Tukey’s post hoc test after ascertaining normality by Shapiro-Wilk test and homogeneity of variances by Levene’s test. Results: The mean Nuclear area of tobacco chewer (C) was the highest and the normal individual (N) was the least. The mean Cytoplasmic area of normal individual (N) was the highest and the tobacco chewer(C) was the least. Conclusions: This study supports and extends the view that cytomorphometric evaluation of keratinocytes can serve as a useful diagnostic adjunct for early detection of oral cancer. Keywords: exfoliative cytology; cytomorphometric; tobacco users; gutkha users.